OP0324 Risk of serious infections in rheumatoid arthritis patients treated with abatacept, rituximab and tocilizumab in denmark and sweden. (12th June 2018) - Grøn, K.L.; Arkema, E.; Glintborg, B.; Mehnert, F.; Østergaard, M.; Dreyer, L.; Nørgaard, M.; Krogh, N.S.; Askling, J.; Heltand, M.; ,
Abstract : Background: Safety concerns have been raised regarding the risk of serious infections (SI) with the different available biologic disease-modifying anti-rheumatic drugs (bDMARDs). Little is known about the risk of SI in patients with rheumatoid arthritis (RA) treated with non-tumor-necrosis-factor-inhibitors (non-TNFi) bDMARDs. Objectives: In RA patients treated in routine care with the three non-TNFi, abatacept, rituximab and tocilizumab 1) to compare crude as well as adjusted incidence rates (IR) of SI after the first year of treatment, and 2) to estimate the relative risk (RR) of SI across these drugs after 1 year of treatment. Methods: Collaborative observational cohort study conducted in Denmark (DK) and Sweden (SE) in parallel. RA patients in DANBIO (DK) and ARTIS/SRQ (SE) who started a non-TNFi treatment Jan 2010 -Dec 2015 were included and their clinical characteristics at baseline were identified. Baseline comorbidities, reimbursed antibiotic prescriptions and incident SI (hospitalisation listing infection as major cause of admission) were identified through linkage to National Patient Registries and Prescription Drug Registries. IR of SI per 100 patient years (adjusted for age and sex) and rate ratios (as estimates of RR, adjusted for additional covariates) during 1 year treatment were assessed via Poisson regression. Results: 8987 treatment episodes were identified (abatacept 2, 725/rituximab 3, 363/tocilizumab 2, 899). Differences in baseline characteristics between the three drugs were observed (table 1). During the first year of treatment, 456 SI were identified. Across all three non-TNFi there was a non-significant tendency towards higher IRs in DK than in SE . Age/sex-adjusted IRs for SI were similar across treatments in each country (abatacept/rituximab/tocilizumab for SE 6.0/6.4/4.7 and for DK 7.1/8.1/6.1, respectively). The 1 year adjusted between-drug comparisons (=RR) were formally non-significant (table 1). Conclusions: The risk of SI across treatment with non-TNFis ranged between 4.7 and 8.1/100 patient years after 1 year, but no significant differences were observed between specific drugs. The numerical between-drug differences may partly be explained by differences in baseline characteristics. Acknowledgements: Partly funded by Foreum and Nordforsk. The Swedish part of the study forms part of the ARTIS safety monitoring programme. For this, ARTIS has or has had agreement with Abbvie, BMS, MSD, Pfizer, Roche, Astra-Zeneca, Eli Lilly, Samsung Bioepis, and UCB. The Danish part of the study forms part of a post-marketing safety surveillance agreement with BMS. Disclosure of Interest: K. Grøn: None declared, E. Arkema: None declared, B. Glintborg Grant/research support from: Biogen, Abbvie, F. Mehnert: None declared, M. Østergaard Grant/research support from: Mikkel Østergaard has received research support and/or consultancy/speaker fees from: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Hospira, Merck, Novartis, Orion, Pfizer, Regeneron, Roche, UCB., L. Dreyer Grant/research support from: L. Dreyer Speakers bureau: UCB, MSD and Janssen Pharmaceuticals, M. Nørgaard: None declared, N. Krogh: None declared, J. Askling Grant/research support from: Johan Askling has or has had research agreements with Abbvie, BMS, MSD, Pfizer, Roche, Astra-Zeneca, Eli Lilly, Samsung Bioepis, and UCB, mainly in the context of safety monitoring of biologics via ARTIS. Karolinska Institutet has received remuneration for JA participating in advisory boards arranged by Pfizer and Eli Lilly. Funding Nordforsk, Foreum, M. Heltand Grant/research support from: Merete L. Hetland has received research funding/consultancy/speakers fee from Abbvie, Biogen, BMS, CellTrion, MSD, Novartis, Orion, Pfizer, Samsung, UCB.